Foreign credential recognition and immigrants’ chances of being hired for skilled jobs – Evidence from a survey experiment among employers - Damelang, Andreas; Ebensperger, Sabine; Stumpf, Felix (Social Forces, 2020)

Gender composition of occupations and occupational characteristics: Explaining their true relationship by using longitudinal data - Damelang, Andreas; Ebensperger, Sabine (Social Science Research, 2020)
This paper analyzes the relationship between the gender composition of occupations and occupational characteristics that describe working arrangements and qualification requirements. While prior studies showed associations between the representation of females in occupations and these occupational characteristics, we are the first to explain their true relationship by applying an analytical research design. In this regard, we add three alternative relationship patterns to the widespread assumption that occupational characteristics affect the representation of females in occupations. First, it is possible that the relationship works in the opposite direction. Second, the relationship does not necessarily have to be causal but can just be a historical connection. Third, the representation of females in occupations may follow a self-enforcing cycle. To put the relationship between the gender composition of occupations and occupational characteristics to the test, we create a unique occupation panel dataset that aggregates individual data from the 1996 to 2012 waves of the German Microcensus. Our results confirm that occupational characteristics determine the representation of females in occupations. Moreover, we find some evidence that the representation of females follows a self-enforcing cycle.
CRIS-Team Scopus Importer:2019-12-13
Keywords: German Microcensus; Longitudinal data; Occupational characteristics; Occupational sex segregation

How family-friendly work arrangements relate to jobs’ gender composition - Damelang, Andreas; Ebensperger, Sabine (2020)

How National Institutions Shape Skilled Immigrants’ Chances of Getting Hired: Evidence from Harmonised Factorial Surveys with Employers in Germany and England - Stumpf, Felix; Damelang, Andreas; Abraham, Martin; Ebensperger, Sabine (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)

How National Institutions Shape Skilled Immigrants’ Chances of Getting Hired: Evidence from Harmonised Factorial Surveys with Employers in Germany and England - Stumpf, Felix; Damelang, Andreas; Abraham, Martin; Ebensperger, Sabine (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
This study provides novel insights into the institutional conditions under which skilled immigrants get hired for skilled jobs in different countries. We argue that immigrants’ hiring chances depend on the interplay between institutions in sending countries, which determine the type of education that immigrants bring, and institutions in receiving countries, which shape employers’ preferences for certain types of education. We develop a research design that considers this interplay and allows us to directly compare how education from sending countries with different institutional arrangements is rated by employers in two countries with widely divergent institutional contexts of reception, Germany and England. Using harmonised factorial surveys, we simulate hiring processes and evaluate the chances of German and English employers inviting foreign-educated immigrants to interviews for jobs commensurate with their education. The survey design makes it possible to experimentally vary the institutional settings in which immigrants acquired their education in the sending country, and isolate their effect on employers’ ratings. Our key finding is that immigrants from sending countries with highly standardised occupation-orientated education systems prevail in the hiring competition, irrespective of the education system in the receiving country.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Educational systems; Foreign education; Labour market; Vignette study; Vocational education and training

Immigrants’ Labour Market Disadvantages Across Western Europe: the Role of Composition and Context - Damelang, Andreas; Ebensperger, Sabine; Stumpf, Felix (Journal of International Migration and Integration, 2021)

The Hiring Prospects of Foreign-Educated Immigrants: A Factorial Survey among German Employers - Damelang, Andreas; Abraham, Martin; Ebensperger, Sabine; Stumpf, Felix (Work Employment and Society, 2019)